Effectiveness of Pictogram Instructions for Donning Smoke Hoods. (September 2018) - Abulhassan, Yousif; Bani Hani, Dania; Davis, Gerard A.
Smoke hoods or respiratory protective emergency devices (RPEDs) are marketed to assist in evacuation from fire emergencies. Many smoke hood manufacturers often rely on pictograms to instruct proper donning procedures to smoke hood users. Comprehending the instructions delivered through pictograms plays an important role in properly donning a smoke hood, and avoiding further injuries or complications from improper usage of the smoke hood. The purpose of this study was to determine the effectiveness of pictogram instructions used by three types of smoke hoods for donning a smoke hood. Results of this study indicate that the type of pictogram instructions have a significant effect on the ability of a user to properly don a smoke hood. While detailed pictogram instructions help users properly don smoke hoods, they also have an impact on the time required to don a smoke hood.